The tumour–stromal interaction between intratumoral c-Met and stromal hepatocyte growth factor associated with tumour growth and prognosis in non-small-cell lung cancer patients - Masuya, D (Nature Publishing Group, 2004)
Immunohistochemical analyses of the effects of hepatocyte growth factor (HGF) and c-Met expression on tumour growth and angiogenesis were performed on 88 patients with non-small-cell lung cancers (NSCLCs). In all, 22 carcinomas (25.0%) were intratumoral HGF-positive, 14 carcinomas (15.9%) were stromal HGF-positive, and 36 carcinomas (40.9%) were intratumoral c-Met-positive. None of the carcinomas were stromal c-Met-positive. Examination of tumour growth revealed that the frequency of tumours with a high Ki-67 index was significantly greater for stromal HGF-positive tumours than for stromal HGF-negative tumours (P=0.0197). The frequency of tumours with a high Ki-67 index was also significantly greater for intratumoral c-Met-positive tumours than for intratumoral c-Met-negative tumours (P=0.0301). However, there was no significant difference in tumour vascularity with relation to intratumoral HGF status, stromal HGF status, and intratumoral c-Met status. The survival rate of patients with intratumoral c-Met-positive tumours was significantly lower than for patients with c-Met-negative tumours (P=0.0095). Furthermore, the survival rate of patients with both intratumoral c-Met-positive and stromal HGF-positive tumours was significantly lower than for patients with either positive tumours, and that of patients with both negative tumours (P=0.0183 and P=0.0011, respectively). A univariate analysis revealed that intratumoral c-Met expression was a significant prognostic factor of NSCLC patients (relative risk=2.642, P=0.0029). The present study demonstrates that tumour–stromal interaction between tumour cell-derived c-Met and stromal cell-derived HGF affects tumour growth and the prognosis of NSCLC patients.